Guidelines for legacy repository migration - Ferreira, Miguel (2013)
Several institutions are currently running long-term digital repositories that have been in operation for several years now. Some of these systems are approaching the end of their life spans and will soon be replaced by the next-generation of long-term digital repository systems. This will unavoidably imply the migration of millions of files, metadata records and terabytes of data from the legacy repository to the newly adopted one. Because of the large scale of this operation, this procedure needs careful planning, validation and support. This paper provides guidelines to support the migration from legacy repository systems by describing the stages, activities and associated risks that comprise this type of endeavor. The presented guidelines are based on a combination of 13 existing methodologies that have been surveyed and unified into a comprehensive multistep methodology.